Acoustic Emission: Sources, Methods and Applications (in Polish), I. MALECKI, J. RANACHOWSKI [Eds.] - OPILSKI, Aleksander (Archives of Acoustics, 1996)
Acoustic emission (AE) is a phenomenon and a method as well. The investigations of this phenomenon, its sources, signals interpretation and their connections with the source character constitute a currently developing subject for research studies. The applications of AE as an investigation method are being developed faster. Ranachowski and Malecki's book introduces both aspects of AE. The book is set of twenty one articles written by different authors, arranged into seven parts.